Selenium and Thyroid Disease: From Pathophysiology to Treatment - Mara Ventura; Miguel Melo; Francisco Carrilho (International Journal of Endocrinology)
Introduction. Selenium is a micronutrient embedded in several proteins. In adults, the thyroid is the organ with the highest amount of selenium per gram of tissue. Selenium levels in the body depend on the characteristics of the population and its diet, geographic area, and soil composition. In the thyroid, selenium is required for the antioxidant function and for the metabolism of thyroid hormones. Methods. We performed a review of the literature on selenium’s role in thyroid function using PubMed/MEDLINE. Results. Regarding thyroid pathology, selenium intake has been particularly associated with autoimmune disorders. The literature suggests that selenium supplementation of patients with autoimmune thyroiditis is associated with a reduction in antithyroperoxidase antibody levels, improved thyroid ultrasound features, and improved quality of life. Selenium supplementation in Graves’ orbitopathy is associated with an improvement of quality of life and eye involvement, as well as delayed progression of ocular disorders. The organic form of selenium seems to be the preferable formulation for supplementation or treatment. Conclusion. Maintaining a physiological concentration of selenium is a prerequisite to prevent thyroid disease and preserve overall health. Supplementation with the organic form is more effective, and patients with autoimmune thyroiditis seem to have benefits in immunological mechanisms. Selenium supplementation proved to be clinically beneficial in patients with mild to moderate Graves’ orbitopathy.